(untitled) (Research, Society and Development, 2024)
Objective: This study investigated blood and salivary parameters in male resistance-training practitioners (RTP) using oxandrolone (OG) and compared with references values and control group (CG), in triplicate. Methods: Blood, saliva, and urine were collected from 22 individuals (OG, n = 11 / CG, n = 11) and analyzed: before oxandrolone (OX) consumption (T1), at cessation of OX use (T2), and three months after cessation of OX use (T3). Complete blood count, lipid profile, metabolites, and enzymes were analyzed from blood samples. Salivary flow, pH, triglycerides, urea, aspartate animotransferase, alanine aminotransferase, phosphorus, and calcium were analyzed from saliva. Urinalysis was used for toxicological screening. Results: A reduced hdl cholesterol level was observed in the og group (24 mg/dL) compared with the reference value (>40 mg/dL) at T2. HDL levels return to normal after cessation AT T3 (49 mg/dL, >40 mg/dL). A higher triglyceride level (177 mg/dL) was verified in OG group compared with the reference value (<175 mg/dL) at T3. Conclusions: The results of this study suggest that oxandrolone use is associated with changes in lipid profiles, including lower HDL levels and higher triglyceride levels, which are characteristic of dyslipidemia. however, while these findings indicate an association, they do not establish definitive causality. further research, including well-controlled longitudinal studies, is needed to confirm the causal relationship between oxandrolone use and dyslipidemia.